Efektivitas Penerapan Kompilasi Hukum Islam Dalam Penyelesaian Perkara Perceraian - Israfil - (Fakultas Hukum Universitas Mataram, 2016)
This research uses juridical sociological approach which study about the norms of law that used to solve divorce cases and the norms’ implementation toward judge’s concideration in giving adjudication. Besides, it study the causal factors of divorce cases in Dompu and kind of law concideration that apllied in judge’s adjudication. The source of data are collected from related documents, recorded interview with the judges and people in Dompu who have an experience of divorce in Dompu, West Nusa Tenggara Barat and know the causal factors of the divorce. Result of the research shows that divorce cases in Dompu is increases from year to year since 2013, which numbers of divorce cases are 479 cases (17.91%). On 2014 the numbers are 691 divorce cases (25.85%). On 2015 the amount are 719 cases (26.89%). Moreover, on 2016 the amount are 785 cases (29.35%). Those divorce cases consists of talak divorce and suit divorce. There are some factors which causes the divorce which gets from Religious Court of Dompu. First is cheating that make the couple in the quarrel all times. Second is one of the couple who works as Indonesian workers overseas (TKI/TKW) which should leave his wife or her husband in a long time.the third factor is the husband cannot fulfill the money for household expenses for his wife and children so the wife bring a lawsuit to the Religious Court of Dompu. Those factors are new tendencies in Dompu along the development of technology especially communication technology. The example is the use of hand phone. This device ease a person (husband/wife) communicate with someone who they cheated with and make a secret love relationship since by using hand phone, the wife or husband will be hard to find out that relationship.